Adaptation of Farmers Regarding Climate Resilient Technologies in Rewa Block of Rewa District in Madhya Pradesh - Chouksey, Rachit; Singh, Kinjulck C.; Singh, Chandrajiit; Birle, Yogesh (Indian Journal of Extension Education, 2021)
Climatic discrepancy is a new challenge to the farming communities. Apart from losses caused due to variable climatic condition, it also affecting the decision making ability of farmers due to lack of awareness and knowledge. Perception and attitude regarding climate change affects farmers’ willingness for adaptation. Adaptation to climate change planning of alternate agricultural management practices in response to change in climate condition well in advance. It has been felt necessary to assess the adaptation of farmers regarding Climate Resilient Technologies. The present study was undertaken in Rewa block of Rewa district. Through random sampling, one hundred twenty farmers from Rewa block were selected purposively from ten villages. The result showed that 45.83 per cent exhibited medium level of adaptation regarding Climate Resilient Technologies. Variables like education, size of land holding, farming experience, farm resources, local personal channels, local cosmopolite channels, mass media contact, innovative proneness, risk orientation, scientific orientation, Knowledge regarding climate change, change proneness had significant relationship with their adaptation and had fair degree of association. Lack of awareness about long term climate change and Lack of timely information related to climate resilient technologies were major constraints perceived by the farmers in adoption to Climate Resilient Technologies.
Keywords: Adaptation; Climate change; Climate resilient technologies; Constraints; Krishi Vigyan Kendra